Foreign plastid sequences in plant mitochondria are frequently acquired via mitochondrion-to-mitochondrion horizontal transfer - Gandini, Carolina Lia (2017)
Angiosperm mitochondrial genomes (mtDNA) exhibit variable quantities of alien sequences. Many of these sequences are acquired by intracellular gene transfer (IGT) from the plastid. In addition, frequent events of horizontal gene transfer (HGT) between mitochondria of different species also contribute to their expanded genomes. In contrast, alien sequences are rarely found in plastid genomes. Most of the plant-to-plant HGT events involve mitochondrion-to-mitochondrion transfers. Occasionally, foreign sequences in mtDNAs are plastid-derived (MTPT), raising questions about their origin, frequency, and mechanism of transfer. The rising number of complete mtDNAs allowed us to address these questions. We identified 15 new foreign MTPTs, increasing significantly the number of those previously reported. One out of five of the angiosperm species analyzed contained at least one foreign MTPT, suggesting a remarkable frequency of HGT among plants. By analyzing the flanking regions of the foreign MTPTs, we found strong evidence for mt-to-mt transfers in 65% of the cases. We hypothesize that plastid sequences were initially acquired by the native mtDNA via IGT and then transferred to a distantly-related plant via mitochondrial HGT, rather than directly from a foreign plastid to the mitochondrial genome. Finally, we describe three novel putative cases of mitochondrial-derived sequences among angiosperm plastomes.